Electricity market regulation: Global status, development trend, and prospect in China. Issue 3 (30th October 2020) - Xu, Chengwei; Wen, Fushuan; Palu, Ivo
Abstract: With ever‐growing electricity consumption, unwanted climate change, and evolving generation mix, some energy policies related to electricity markets are enforced in various countries to cope with emerging challenges in the energy sector. Electricity market regulation, which is required to keep pace with the continuous development of power industry restructuring and electricity market operation, is also evolving. To help researchers and policy makers have a better understanding of the state‐of‐the‐art electricity market regulation, the aim is to survey the latest progress, as well as the development trends in this field in the United States, Australia, United Kingdom, and France, which have mature and widely recognized electricity markets around the globe. Subsequently, the progress of the electricity market reform in China is described, and the status, drawbacks, and prospect of the electricity market regulation in China presented.